Positive Educational actions and Healthy Sustainable Development. - de Villarreal, Maider Perez (Advances in Social Sciences Research Journal, 2015)
Up to the 21st century, school education is in a state of crisis as a sequence of globalization when the neoliberal model of development pushes to question the right to a good public education (Reid, 1998). The ideal of a public education defined about two centuries ago (Hamilton & Zufiaurre, 2014) is getting lost because of international pressures for competition and dominance of some against the majority. But, living as we are in a diverse world, the misunderstandings, misperceptions and mistakes, regarding the social and natural world we inhabit, are forced to evolve to a context of discursively, morally and socially, ecologically, materially and economically sustainable and socially and personally healthy. School education has something to do about this. Diversity is the curriculum organizer today, and diversities, are opened to a world of multiple interactions, mixed identities and multiple senses of belonging. At this point, we have to turn our lens. Positive psychology and Positive actions in education can contribute to promote good interaction, democratic participation and a healthy balanced sustainable atmosphere of work. And this is important to promote collaboration, engagement, inclusion and equality. *Problem statement: Students, teachers, families, communities, develop in a context of diversities. They can be pushed to share, participate, cooperate and socialize while learning together. *Purpose of the study, Findings & Results: Our research reflects on positive experiences developed with teachers, students, and families, in 25 Infant, Primary and Compulsory secondary schools in Navarra, around 260 teachers and diverse families, from 2012 to 2014 (two years). This which has been framed on the basis of an E.U. Project POSITIVITIES, is exemplified in how can we organize the teaching and learning of a natural phenomenon: “bees in extinction” to be worked out with 10 to 12 years old boys and girls in a constructive school atmosphere. *Method: Pilot Study to analyze how an online platform on Positive psychology helps teachers to develop socio-emotional skills, encourage to work interactively while at the time, stimulating wellbeing and self-esteem. *Conclusions and Recommendations: Positive Psychology and Positive Pedagogical actions developed at school education contribute to promote good interaction, democratic participation and a healthy balanced sustainable atmosphere of work to promote equal roles for women, the culturally diverse, the diverse capabilities and abilities…